Innovation in Small and Medium Enterprises in Vietnam - Tran, Trang Mai; Vu, Ngoc Minh Thi (Darul Yasin Al Sys, 2024)
In a rapidly evolving market context, innovation plays a crucial role in the success of Small and Medium Enterprises (SMEs) in Vietnam. This study delves into the significance of business innovation, particularly in light of the need for SMEs to cultivate new competitive advantages amidst a growing number of similar competitors. For Vietnamese companies, innovation is not merely an option but a necessity for sustainable growth. This article focuses on exploring the advantages, disadvantages, opportunities, and risks associated with innovation in Vietnamese SMEs.